Contribution to the study of habitat diversity in Western Stara Planina Mountain (Bulgaria) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
In connection with the creation of the Bulgarian part of the European ecological network NATURA 2000 eleven types of habitats of European significance have been determined in the Stara Planina Mt. (Western), the northernmost part of Znepole region and the westernmost part of Sofia region. Two habitats (6240 – Sub-pannonic steppe grasslands and 40А0 – Sub-continental peri-pannonic scrub) are of a priority according to the Directive 92/43/EEC. The habitats most commonly met are – 6510 (Lowland hay meadows), followed by 6240 (Sub-pannonic steppe grasslands) and 6210 (Semi-natural dry grasslands and scrubland facies on calcareous substrates). The rest of the habitat types - 6520, 62A0 and 6410 have been ascertained twice or thrice and 6440, 6230 and 6110, 8210 were found as single formations. The habitats studied are known for Bulgaria, but their precise localities in the Western Stara Planina are reported for the first time.
Keywords: habitats, Stara Planina Mountain (Western), Bulgaria.